Chinese classics records of the historian - Sima Qian (Chinese classics stories, 2017)
Records of the Historian is the first Chinese book on general history ever written in the biographical style. Besides,being a great literary work,Records of the Historian opens a new horizon of recording and narrating historical events in the form of individual biographies.